2021
DOI: 10.7554/elife.68610
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic analyses of organelles highlight the nucleus in age-related trait heritability

Abstract: Most age-related human diseases are accompanied by a decline in cellular organelle integrity, including impaired lysosomal proteostasis and defective mitochondrial oxidative phosphorylation. An open question, however, is the degree to which inherited variation in or near genes encoding each organelle contributes to age-related disease pathogenesis. Here, we evaluate if genetic loci encoding organelle proteomes confer greater-than-expected age-related disease risk. As mitochondrial dysfunction is a 'hallmark' o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…For instance, TFs are strongly enriched for haploinsufficient disease associations, resulting from the loss of one functional allele, and are depleted of loss-of-function variants in the general population 7 , 8 . Genome-wide association studies have revealed thousands of trait-associated variants, many of which likely act by modulating RE activity and gene expression levels 9 , 10 ; trait-associated variants are also highly enriched around TF genes 11 , 12 . Both experimental and population-level data suggest that such common variants show per-allele effects on gene expression of up to 10–15% (refs.…”
Section: Mainmentioning
confidence: 99%
“…For instance, TFs are strongly enriched for haploinsufficient disease associations, resulting from the loss of one functional allele, and are depleted of loss-of-function variants in the general population 7 , 8 . Genome-wide association studies have revealed thousands of trait-associated variants, many of which likely act by modulating RE activity and gene expression levels 9 , 10 ; trait-associated variants are also highly enriched around TF genes 11 , 12 . Both experimental and population-level data suggest that such common variants show per-allele effects on gene expression of up to 10–15% (refs.…”
Section: Mainmentioning
confidence: 99%
“…Numerous studies have emphasized the transformative impact of adjusting the TF dose on molecular and cellular states 9,13,15,6467 . The significant degree of cellular heterogeneity typically observed upon TF overexpression in ex vivo experiments contrasts however with the precise control of cell fate alterations observed in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Published mtscATACseq data used for chrM:302 analysis can be obtained via approval from dbGaP. Gene-sets for enrichment analyses can be obtained using COMPARTMENTS (https://compartments.jensenlab.org) and MitoCarta 2.0 (https://www.broadinstitute.org/files/shared/metabolism/mitocarta/human.mitocarta2.0.html ) as described previously (Gupta et al, 2021). The GRCh37 and GRCh38 reference genomes as well as other standard reference data are available via the GATK resource bundle: https://gatk.broadinstitute.org/hc/en-us/articles/360035890811-Resource-bundle.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Telomerase (TERT) is in the vicinity of one locus, however fine-mapping did not provide additional evidence for its causality (Supplementary table 3). We next tested mtCNcorr for heritability enrichment in genes associated with organelles or organs using stratified LD-score regression (S-LDSC, Finucane et al, 2015Finucane et al, , 2018Gupta et al, 2021), Methods). Encouragingly, the most significant organelle enrichment was seen for the mitochondrion (Supplementary figure 4C).…”
Section: Determinants Of Mtdna Copy Number Variationmentioning
confidence: 99%
See 1 more Smart Citation